ANALISIS LAPORAN ARUS KAS TERHADAP LIKUIDITAS PADA PT. KIMIA FARMA TBK TAHUN 2018 SAMPAI DENGAN TAHUN 2020 - Jitmau, Fanny; Marpaung, Christine Sada M (LPPM Politeknik Saint Paul Sorong, 2021)
The purpose of this study is to identify the cash flow statement in order to assess the company's liquidity. This form of research is descriptive, uses secondary data, and uses both qualitative and quantitative analysis as a data gathering technique at PT.Kimia Farma (Persero) Tbk. The data analysis method employed is to calculate the operating cash flow ratio (AKO), interest cash flow coverage ratio (CKB), capital expenditure ratio (PM), and total debt ratio from the company's cash flow statement (TH). The calculation's results show that the company's liquidity PT. Kimia Farma (Persero) Tbk. from 2018 to 2020 will be determined by the findings of the analysis of the cash flow statement.